The value of exercise stress testing in prediction of angiography amongst South African patients using quantitative scoring systems - Premsagar, Preesha; Aldous, Colleen; Esterhuizen, Tonya (SA Heart Journal, 2021)
Background: Accurate pre-test assessment of high risk patients may increase positive yield on angiography. Exercise stress testing (EST) prediction of angiography, may be evaluated by Duke Treadmill Score (DTS), and Synergy between Percutaneous Coronary Intervention with Taxus and Cardiac Surgery (SYNTAX) score, respectively. Aim: To investigate the value of EST in prediction of angiography amongst South African patients using quantitative scoring systems. Methods: The DTS and SYNTAX score were compared in patients with high risk pre-test assessments selected for angiography. Logistic regression modelling determined the odds ratio of abnormal angiograms using EST as a predictor. Results: Pre-test assessment of 525 suspected coronary artery disease patients, indicated angiography in 131 high risk individuals. The positive yield of abnormal angiograms was 58.0%, with no correlation between DTS and SYNTAX scores (Pearson’s correlation coefficient = 0.113, p=0.200). There was low predictive probability on receiver-operator-curve for DTS when compared to angiogram results (area under curve (AUC)=0.529, p=0.574), and SYNTAX categories (AUC=0.432, p=0.378). Chi-square tests had no significance between angiography and EST (all p-values >0.05). However DTS predicted abnormal angiograms with odds ratio of 1.92 when relevant cardiovascular risk factors (smoking, BMI, age) were added. Conclusion: Pre-test assessment of high risk patients represented a homogenous group with prevalent cardiovascular risk factors. However, the high risk group had no relationship between DTS and SYNTAX scores, indicating DTS alone discounts risk factors. Modelling accounted for DTS limitation by demonstrating an obese, elderly smoker with high risk category DTS is 1.92 times more likely to have an abnormal angiogram.